Menelusuri Akar Sejarah Pluralitas Agama di Kota Sukabumi - Gemilang, Gian Fajar; Darmawan, Wawan (Universitas Hamzanwadi, 2024)
The phenomenon of tolerance in social life creates a sense of harmony and peace for religious people. The dynamic social situation also influences the attitude of the community in responding to the understanding of the tradition of each community. This research attempts to identify the history of religious plurality in Sukabumi City with a focus on factors that influence current religious practices. Through a historical methodology approach, this research aims to identify whether tolerance has existed since the colonial period or is a new construction of the current leaders and rulers. The results showed that the development of religious communities in Sukabumi City was shaped through the role of religious leaders as spiritual leaders and messengers of peace to the community. In addition, government support and the need for adequate worship facilities contribute to creating an inclusive atmosphere for all religious communities. Regulations related to religious practices and traditions also play an important role in strengthening interfaith harmony. This harmony is known to arise from a deep understanding of each other's beliefs and a sense of love manifested in human relationships.